Effects of symmetry, methyl groups and serendipity on intramolecular vibrational energy dispersal - Tuttle, William D.; Gardner, Adrian M.; Whalley, Laura E.; Kemp, David J.; Wright, Timothy G. (Royal Society of Chemistry, 2018)
We consider two key parameters that have been proposed to be important for vibrational energy delocalization, closely related to intramolecular vibrational redistribution (IVR), in molecules. These parameters are the symmetry of the molecule, and the presence of torsional (internal rotor) modes of a methyl group. We consider four para-disubstituted benzene molecules and examine their vibrational character. The molecules selected are para-difluorobenzene, para-chlorofluorobenzene, para-fluorotoluene, and para-xylene. This set of molecules allows the above parameters to be assessed in a systematic way. The probe we use is zero-electron-kinetic-energy (ZEKE) spectroscopy, which is employed in a resonant scheme, where the intermediate levels are selected vibrational levels of the S1 excited electronic state, with wavenumbers up to 1300 cm 1. We conclude that symmetry, and the presence of a methyl groups, do indeed have a profound effect on “restricted” IVR at low energies. This is underpinned by serendipitous coincidences in the energies of the levels, owing to small shifts in vibrational wavenumbers. Additionally, methyl groups play an important role in opening up new routes for coupling between vibrations of different symmetry, and this is critical in the transition to “statistical” IVR at lower energies for molecules that contain them. Further, the presence of two methyl groups in the symmetrically-substituted p-xylene causes more widespread IVR than does the single methyl group in the asymmetrically-substituted p-fluorotoluene.